Impact of error fields and error field correction on heat fluxes in SPARC - S. Munaretto; A. Kleiner; R.M. Churchill; D. Corona; T. Looby; M. Scotto d’Abusco; A. Wingen (Nuclear Fusion)
Using a single toroidal array of coils to reduce the $m,n = 2,1$ resonant error field (EF) produced by the misalignment of the axisymmetric coils in SPARC can result in the enhancement of the local divertor heat fluxes. Managing high divertor heat fluxes ( $q_{\parallel} \simeq 10$ GW m ^−2 ) poses a challenge for compact tokamak devices such as SPARC. The presence of non-axisymmetric magnetic field perturbations adds complexity to the problem by generating intricate 3D edge magnetic topologies that alter the heat flux distributions on the target plates. The aim of this work is to investigate the impact of the EF correction (EFC) on the heat fluxes at the divertor plates in SPARC. The MHD code M3DC1 has been used to simulate the 3D magnetic perturbations generated by the shift and tilt of several axisymmetric coils within specified tolerances, as well as from the array of EFC coils located at the midplane. Using a heuristic model that extends the concept of an axisymmetric heat flux layer to 3D plasmas, the resultant heat flux distributions is derived from magnetic footprints calculated with the MAFOT code. The results show that the EFC could either decrease or further enhance the local heat flux when used to correct the $m,n = 2,1$ resonant EF to enhance the core plasma performance.